Rancang Bangun Game Pet Venture Quest Menggunakan Game Development Life Cycle (GDLC) untuk Mendukung Pembelajaran Motorik Anak - Baharuddin, Muh. Yassar Afaaf; Zulfajrin, Zulfajrin; Irmayana, Andi; Arifin, Suci Ramadhani (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2024)
Education for children in the digital era increasingly emphasizes the development of learning solutions, particularly through educational games. These games provide an interactive learning experience and support the motor skills development of elementary school-aged children. The Game Development Life Cycle (GDLC) approach is crucial in the development of effective educational games. This research designed “Pet Venture Quest” using the GDLC approach, with the aim of supporting children's motor skill development and measuring its positive impact. The results of this study are expected to provide guidance for educational game developers and education practitioners in maximizing technology to support children's motor skill development through games.